An immigrant nation seeks cohesion : Australia from 1788 / James Jupp. - Jupp, James (Anthem studies in Australian politics, economics and society., 2018)
Australia is a unique society, created from immigration planned by the state and, for almost a century, organised and recruited through the governments of the British Empire. In the formative days it depended on convict labour from England and Ireland, whereas the United States depended on slave labour from Africa. In subsequent years most Australians were British subjects whereas this ceased to be so for Americans upon their independence. However in recent years this British character has progressively been abandoned with the admission of a wide from other societies. This has created a multicultural society, although one in which the English language remains dominant and British "values' remain praised at least by the conservative side of politics Australia is remote from Britain despite many transport links and investments. Its neighbours are Asians or Pacific Islanders, with only New Zealand as a much smaller British neighbour many miles away.This leads to contradictory situations such as the increasing Asian intake of immigrants and of Asian and especially Chinese business and investment. Although Immigration still remains government controlled as throughout the past but it no longer favours British settlers as it once did. Apart from local neighbours arriving for temporary or permanent residence it also faces the fact that British naval and military force is no longer relevant in the region. The closest protective Ally has become the United States, but the growing powers include China, India and the small but threatening Communist republic of North Korea, armed with nuclear rockets aimed on Australian potential targets for the first time since the end of the war with Japan in 1945. From a relatively safe and stable society, Australia faces new dilemmas. However, even in the past' emphasis on building a compatible society was not achieved without many tensions and problems.